Green BIM : successful sustainable design with building information modeling - Krygiel, Eddy, 1972-; Nies, Brad, 1971- (Indianapolis, Ind. : Wiley Pub., 2008)
"Meet the challenge of integrating Building Information Modeling and sustainability with this guide, which pairs these two revolutionary movements to create environmentally friendly design through a streamlined process. Written by an award-winning team that has gone beyond theory to lead the implementation of Green BIM projects, this comprehensive reference features practical strategies, techniques, and real-world expertise so that you can create sustainable BIM projects, no matter what their scale. From basic concepts, to sophisticated test methodologies, to improved workflows, this timely book offers a wealth of information you can implement right away."--BOOK JACKET.
Introducing green -- Building information modeling -- Integrated design teams -- Methodology for sustainable solutions -- Sustainable BIM : building form -- Sustainable BIM : building systems -- The future of BIM and sustainable design.
Includes index.
ARC
Keywords: Sustainable buildings -- Design and construction; Building information modeling; Building -- Data processing